A simple approach to the synthesis of Cu1.8S dendrites with thiamine hydrochloride as a sulfur source and structure-directing agent - Yan, Xiaoliang; Li, Sha; Pan, Yun-xiang; Yang, Zhi; Liu, Xuguang (Beilstein Journal of Nanotechnology, 2015)
A facile, green and environmental-friendly method for preparing Cu1.8S dendrites was developed. Copper nitrate and thiamine hydrochloride were selected as the starting materials in the water phase under hydrothermal conditions. No addition of a surfactant or a complex reagent was required for the synthesis of the Cu1.8S dendrite structures. Thiamine hydrochloride was employed as a sulfur source and structure-directing agent. The growth mechanism of Cu1.8S is tentatively discussed based on the experimental and computational results.
Keywords: biomaterials; crystal growth; crystal structure; Cu1.8S dendrite; hydrothermal